Genetic Divergence in Eucalyptus camaldulensis Progenies in the Savanna Biome in Mato Grosso, Brazil. - Reginaldo Brito da Costa; Jeane Cabral da Silva; Leandro Skowronski; Michel Constantino; Hemerson Pistori; Jannaína Velasques da Costa Pinto (PLoS ONE, 2016)
Assessing the parental genetic differences and their subsequent prediction of progeny performance is an important first step to assure the efficiency of any breeding program. In this study, we estimate the genetic divergence in Eucalyptus camaldulensis based on the morphological traits of 132 progenies grown in a savanna biome. Thus, a field experiment was performed using a randomized block design and five replications to compare divergences in total height, commercial height, diameter at breast height, stem form and survival rate at 48 months. Tocher's clustering method was performed using the Mahalanobis and Euclidian distances. The Mahalanobis distance seemed more reliable for the assessed parameters and clustered all of the progenies into fourteen major groups. The most similar progenies (86 accessions) were clustered into Group I, while the most dissimilar (1 progeny) represented Group XIV. The divergence analysis indicated that promising crosses could be made between progenies allocated in different groups for high genetic divergence and for favorable morphological traits.